Myth in human history - Voth, Grant L.; Teaching Company (Chantilly, VA : Teaching Co., 2010)
"In 36 half-hour lectures, this course explores myths from around the world, focusing in particular on myths outside the Greco-Roman world..."--Guidebook.
disc 1. Myth and meaning ; The continuing importance of myth ; Creation myths ; Mesopotamian creation--Enuma Elish ; Hebrew creation myths ; Emergence and world-parent creation myths -- disc 2. Cosmic egg and ex nihilo creation myths ; Earth-diver and dismembered God creation myths ; Mesopotamian and Hebrew flood myths ; Other flood myths ; Myths of cosmic destruction ; Greek and Norse pantheons -- disc 3. The great Goddess remembered? ; The Goddess--Inanna and Dumuzi ; The Goddess--Isis and Osiris ; The eclipse of the Goddess ; Shamans and vegetation Gods ; Sky Gods and earth Goddesses -- disc 4. Creator Gods ; Gods and Goddesses of India ; Hero myths ; Mythic heroes--Gilgamesh ; Mythic heroes--King Arthur ; Mythic heroes--Jason and the Argonauts -- disc 5. The monomyths of Rank and Campbell ; Mythic heroes--Mwindo ; Female heroes--Demeter and Hester Prynne ; Female heroes--Psyche and Beauty ; The trickster in mythology ; Tricksters from around the world -- disc 6. Native American tricksters ; African tricksters ; Mythic tricksters--Eshu and Legba ; The places of myth--rocks and lakes ; The places of myth--mountains ; The places of myth--sacred trees.
DVD format.
Instructor: Professor Grant L. Voth, Monterey Peninsula College.
Producer, Tony Hidenrick ; academic content supervisor, Marcy McDonald and Susan Dryer ; editors, Tony Hidenrick and Maureen Tumulty.
Keywords: Mythology; Gods; Goddesses